SENAM DON DAP DAPE EFEKTIF MENINGKATKAN VO2max LANSIA DARI PADA SENAM KEBUGARAN JASMANI - Surya Wisesa, Kadek Arya Putra; Astrawan, I Putu; Suparwati, Komang Tri Adi; Prianthara, I Made Dhita; Wahyuni Novianti, I Gusti Ayu Sri (PHYSIO MOVE JOURNAL, 2025)
AbstractThe increasing elderly population leads to a higher risk of functional decline, including reduced VO₂max, which reflects physical fitness. Physical exercise, such as aerobic gymnastics, is an effective intervention to improve VO₂max in older adults. This study aimed to compare the effectiveness of Don Dap Dape exercise and Physical Fitness Gymnastics in increasing VO₂max among the elderly in Banjar Kerta Bumi, East Denpasar. This research employed an experimental design with a two-group pre-test and post-test approach. A total of 20 elderly participants meeting the inclusion criteria were divided into two groups of 10. Group I performed Physical Fitness Gymnastics, while Group II performed Don Dap Dape gymnastics for four weeks. VO₂max was measured using the Six Minutes Walking Test, and the data were analyzed using the independent sample t-test. The results showed a significant increase in VO₂max in both groups; however, Group II (Don Dap Dape) showed a higher increase (31.23%) compared to Group I (22.21%), with a p-value of 0.032. These findings indicate that Don Dap Dape gymnastics is more effective in enhancing VO₂max in the elderly. This study recommends Don Dap Dape gymnastics as an alternative physical activity to improve physical fitness in older adults.Keywords: elderly, VO₂max, Don_Dap_Dape_exercise, physical_fitness, cardiorespiratory_endurance AbstrakPeningkatan populasi lansia berdampak pada meningkatnya risiko penurunan kapasitas fungsional, salah satunya VO2max yang mencerminkan kebugaran jasmani. Latihan fisik seperti senam dapat menjadi intervensi efektif untuk meningkatkan VO2max pada lansia. Penelitian ini bertujuan untuk mengetahui efektivitas senam Don Dap Dape dibandingkan Senam Kebugaran Jasmani dalam meningkatkan VO2max pada lansia di Banjar Kerta Bumi, Denpasar Timur. Penelitian ini menggunakan desain eksperimen dengan pendekatan two group pre-test and post-test. Sebanyak 20 responden lansia yang memenuhi kriteria inklusi dibagi ke dalam dua kelompok, masing-masing 10 orang. Kelompok I mengikuti Senam Kebugaran Jasmani dan kelompok II mengikuti Senam Don Dap Dape selama empat minggu. Pengukuran VO2max dilakukan menggunakan Six Minutes Walking Test, dan analisis data menggunakan uji independent sample t-test. Hasil penelitian menunjukkan bahwa kedua kelompok mengalami peningkatan VO2max secara signifikan, namun peningkatan pada kelompok Senam Don Dap Dape (31,23%) lebih tinggi dibandingkan kelompok Senam Kebugaran Jasmani (22,21%), dengan nilai p = 0,032. Hasil ini menunjukkan bahwa Senam Don Dap Dape lebih efektif dalam meningkatkan VO2max pada lansia. Penelitian ini merekomendasikan Senam Don Dap Dape sebagai alternatif latihan fisik bagi lansia untuk meningkatkan kebugaran jasmani.Kata kunci: lansia, VO2max, senam_Don_Dap_Dape, senam_kebugaran, kebugaran_jasmani